Probable reference evapotranspiration for Chapecó, Santa Catarina, Brazil - Back, Álvaro José (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Evapotranspiration data are important for water resources management and irrigation design and management. The present work aimed to determine the probable reference evapotranspiration for Chapecó, Santa Catarina. Daily data from 07/01/1973 to 11/30/2016 from the Chapecó meteorological station were used. Daily evapotranspiration was calculated using the Penman-Monteith method and grouped into pentads. The average, maximum and minimum values per pentad as well as average values for dry and rainy days were determined. The Beta probability distribution was adjusted for each pentad and the goodness of fit was evaluated with the Kolmogorov-Smirnov test and determination of the maximum error, mean error, and standard error of the estimate. Probable ETo values were determined for 50, 75, 80, 90, and 95% probability. The average monthly values obtained were 18 to 80% higher than those normally used in the region, with the greatest differences occurring in the winter months. It is observed that the mean values of ETo per pentad vary from 1.60 mm day-1 to 4.84 mm day-1. The ETo values of dry days are on average 38% higher than those of rainy days. The ETo with 75% of probability presents values of 10 to 32% superior to the values of ETo with 50% of probability, being the differences bigger in the winter months. For the design of irrigation projects in the Chapecó region, it is recommended to use ETo values with 75% probability.